2014
DOI: 10.1002/path.4452
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of UDP‐glucosylceramide synthase in mice prevents Gaucher disease‐associated B‐cell malignancy

Abstract: Clonal B-cell proliferation is a frequent manifestation of Gaucher disease - a sphingolipidosis associated with a high risk of multiple myeloma and non-Hodgkin lymphoma. Gaucher disease is caused by genetic deficiency of acid β-glucosidase, the natural substrates of which (β-d-glucosylceramide and β-d-glucosylsphingosine) accumulate, principally in macrophages. Mice with inducible deficiency of β-glucosidase [Gba(tm1Karl/tm1Karl)Tg(MX1-cre)1Cgn/0] serve as an authentic model of human Gaucher disease; we have r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 56 publications
(96 reference statements)
3
67
0
Order By: Relevance
“…These data are also consistent with recent findings regarding a reduced risk of B-cell cancers with substrate reduction in another model of Gaucher’s disease. 23 …”
Section: Discussionmentioning
confidence: 99%
“…These data are also consistent with recent findings regarding a reduced risk of B-cell cancers with substrate reduction in another model of Gaucher’s disease. 23 …”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, mice bearing large tumors had less GlcCer and glucosylsphingosine accumulation than those with small tumors. In this model, the monoclonal protein disappeared from mice treated with eliglustat; moreover, a striking reduction in lymphoproliferation was observed, with no plasmocytoma or lymphoma [68]. A more recent study on monoclonal immunoglobulin (Ig) in GD showed that in 17 of 20 patients with GD and six of six Gaucher mice, the clonal Ig was specific for glucosylsphingosine.…”
Section: Pathophysiologymentioning
confidence: 99%
“…In the case of GBA-deficient Limp2 −/− mice, plasma GlySph was 4-fold increased, but no clear abnormalities in other lyso-GSLs are detected. Insufficient plasma of GD1 mice was available for complete lipid analysis following that of GlcSph which was found to be 170-fold elevated [26]. In the case of Krabbe mice, plasma galactosylsphingosine (GalSph, more than 90% of total GlySph) was about~12-fold increased, but other lyso-GSLs appeared normal.…”
Section: Abnormalities In the Plasma Of Lsd Mouse Modelsmentioning
confidence: 99%
“…Consequently, it remains unclear whether the GlcSph contributes to the symptoms observed in GD patients, such as occurrence of hemolysis, multinucleated macrophages, neuropathology, growth retardation, bone deterioration and chronic low grade inflammation [6]. Recent investigations by Cox and coworkers have revealed an intriguing correlation between the occurrence of lymphoma in Gba tm1Karl/tm1Karl Tg(Mx1-cre)1Cgn/0 mice and GlcSph levels [26,45]. Currently a direct role for elevated GlcSph in the symptomatology of GD has not yet been unequivocally demonstrated.…”
Section: Modelmentioning
confidence: 99%